高等教育成本补偿与担机制的经济研究 = Sharing the cost of higher education : an economic analysis - 陈忠飞 Chen, Zhong Fei (2008)
This study aims to measure the private and social costs and benefits form investment in higher education. More importantly, it aims to probe into the basic features and trend of development of higher education in China; the theoretical foundation and principles of, as well as resistance to, cost compensation and cost sharing in higher education.